Top income shares and aggregate wealth-income ratio in a two- class corporate economy - Soon Ryoo (University of Massachusetts, Department of Economics, 2016)
This paper examines some determinants of top income shares and the aggregate wealth-income ratio in the United States. The paper, first, points out the difficulties in Piketty's neo-classical version of explanation of US income inequality, which stresses the effect of the rising aggregate wealth-income ratio and high elasticity of factor substitution. Second, the analysis, based on a Cambridge two-class model along the lines of Kaldor (1955/56, 1966) and Pasinetti (1962), highlights the role of financialization in increasing inequality. Third, the analysis suggests that the rise in the aggregate wealth-income ratio from 1980 to 2007 in the US is explained mostly by asset price inflation, not by technical relations. Finally, the analysis examines the effects of the slowdown in capital accumulation on income distribution and wealth-income ratios, which are very different from those in Piketty's Capital in the twenty first century.
Keywords: E12; E21; E25; E44; 330; top income share; wealth-income ratio; financialization; top management pay; stock-flow consistency